Upfront allogeneic hematopoietic cell transplantation (HCT) versus remission induction chemotherapy followed by allogeneic HCT for acute myeloid leukemia with multilineage dysplasia: A propensity score matched analysis. Issue 1 (29th November 2018) - Konuma, Takaaki; Harada, Kaito; Yamasaki, Satoshi; Mizuno, Shohei; Uchida, Naoyuki; Takahashi, Satoshi; Onizuka, Makoto; Nakamae, Hirohisa; Hidaka, Michihiro; Fukuda, Takahiro; Ohashi, Kazuteru; Kohno, Akio; et al.
Abstract : The efficacy of induction chemotherapy before allogeneic hematopoietic cell transplantation (HCT) for patients with acute myeloid leukemia with multilineage dysplasia (AML‐MLD) is unclear. Some patients with AML‐MLD have received upfront HCT without prior induction chemotherapy. To compare the transplant outcomes between patients who received upfront HCT and those who received induction chemotherapy followed by allogeneic HCT for AML‐MLD, we retrospectively analyzed the Japanese registration data of 1445 adult patients who had received allogeneic HCT between 2007 and 2016. Propensity score matching identified 269 patients in each cohort. There were no significant differences in overall survival between the two groups. The cumulative incidence of leukemia‐related mortality was significantly lower in patients who received upfront HCT than those who received induction chemotherapy before HCT. In the subgroup analyses, upfront HCT had a significantly reduced incidence of leukemia‐related mortality among patients aged between 60 and 70 years, those with a lower white blood cell count at diagnosis (<3000/μL), and poor cytogenetic risk, and those who received myeloablative conditioning and cord blood transplantation. Our results suggested that induction chemotherapy before HCT did not have any benefits of survival after HCT for AML‐MLD. Upfront HCT contributed to the reduced incidence of leukemia‐related mortality after HCT. Upfront HCT should be considered for patients with AML‐MLD who are eligible for allogeneic HCT.